2016
DOI: 10.7862/rf.2016.3
|View full text |Cite
|
Sign up to set email alerts
|

On the Evolution of Academic Staff Structure in a University Setting

Abstract: This paper models the academic staff structure in a university as a system of stocks and flows in a three-dimensional space, R 3 . The stocks are the number of academic staff in a particular state at a given time and the flows are the staff moving between any two states over an interval of time. The paper places emphasis on the grade-specific completion rates of Graduate Assistants, who choose to study in the university in which they are employed for higher degrees. The study describes the evolution of structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The art of applying mathematical techniques to a wide variety of problems in education has gained prominence in the literature (for instance, [Jimenez and Salas-Velasco (2000)]; [Mancebon and Muniz (2008)]; [Nicholls (2009)]; [Ekhosuehi and Osagiede (2013)]; [Johnes (2015)]; [Ekhosuehi (2016)]). These studies have shown that research in education is a worthwhile venture to educational planners, managers and consumers of education.…”
Section: Introductionmentioning
confidence: 99%
“…The art of applying mathematical techniques to a wide variety of problems in education has gained prominence in the literature (for instance, [Jimenez and Salas-Velasco (2000)]; [Mancebon and Muniz (2008)]; [Nicholls (2009)]; [Ekhosuehi and Osagiede (2013)]; [Johnes (2015)]; [Ekhosuehi (2016)]). These studies have shown that research in education is a worthwhile venture to educational planners, managers and consumers of education.…”
Section: Introductionmentioning
confidence: 99%